Effect Of Cost Of Goods Sold On Clove Commodity Farmers’ Income With Momosad As A Moderating Variable - Sabrina Mutiarahma Mamonto; Tri Handayani Amaliah; Ronald S. Badu (STIE Amkop Makassar, 2026)
This research aims to analyze the effect of cost of goods sold COGS) on clove farmers’ income and to examine the role of momosad as a moderating variable in the relationship between COGS and clove farmers’ income in Buyandi Village, Modayag Subdistrict. This research employs a quantitative approach with a survey method through questionnaire distribution. The population consisted of all clove farmers in Buyandi Village, Modayag Subdistrict. Using a nonprobability sampling technique, a sample of 50 clove farmers who met the criteria was selected. Data analysis techniques employed multiple linear regression with a moderated regression approach, assisted by SPSS version 20. The results show that the cost of goods sold has a positive and significant effect on farmers’ income. Furthermore, momosad, as a form of traditional mutual cooperation, directly demonstrates a positive and significant effect on farmers’ income. However, the moderation test results indicate that momosad provides a negative and significant influence on the relationship between COGS and farmers’ income. This suggests that although momosad directly improves production process efficiency, as a moderating variable, momosad weakens the relationship between COGS and farmers’ income. These findings indicate that social factors cannot always strengthen economic relationships based solely on cost calculations.",